New Integrated Science for Nigerian Junior Secondary Schools Pupils' Book 1 - Jegede, O J et al (Macmillan Nigeria Publishers Ltd, 1989)
The main objective of the FME core curriculum for integrated science, junior secondary schools, are the learning of the skills of observing, reporting ,organizing information, predicting and experimenting.
Keywords: Juvenile literature-Integrated Science-Study and teaching (Secondary)-Nigeria (English)